Bullying and ART Nonadherence Among South African ALHIV: Effects, Risks, and Protective Factors. (1st April 2021) - Casale, Marisa; Cluver, Lucie; Boyes, Mark; Toska, Elona; Gulaid, Laurie; Armstrong, Alice; Shenderovich, Yulia; Rudgard, William E.; Zhou, Siyanai; Langwenya, Nontokozo
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Identifying risk and protective factors for adolescent antiretroviral therapy (ART) adherence is a public health priority, given high HIV-related mortality in this population. An area that merits further investigation is the relationship between bullying victimization, mental health problems, and ART nonadherence among adolescents living with HIV (ALHIV). However, no known studies assess effects of bullying on adolescent nonadherence or risk and protective factors that could moderate this relationship. Setting: This study investigates (1) the direct longitudinal relationship between bullying exposure and ART nonadherence, and the indirect relationship via psychological distress, and (2) potential risk and modifiable protective factors moderating these pathways, among vertically and horizontally infected ALHIV who initiated treatment across 53 public health care facilities in a South African health district. Methods: Survey data were collected at 2 time points, between 2014 and 2017, with 1046 ALHIV (94% retention). Various mediation and moderated mediation models were run as part of a staged analysis approach. Results: A significant longitudinal relationship was found between bullying victimization and nonadherence, operating indirectly through psychological distress [ B = 0.07; 95% confidence interval (CI): (0.03 to 0.13)]. Moderation analyses indicated that older adolescents exposed to bullying are more at risk of nonadherence [ B = 0.52; 95% CI: (0.07 to 0.97) P < 0.05], and parental monitoring is a potential protective factor buffering indirect effects of bullying on nonadherence [ B = −0.22; 95% CI: (−0.42 to −0.02) P < 0.05]. Conclusions: These findings underscore the importance of interventions that address bullying and psychological distress, and strengthen parental monitoring, particularly among older ALHIV.